Evaluating the Serofast State in Syphilis: A Study of Clinical Characteristics, Immunological Markers, and HIV Status - Lifesia Natali Lidjaja; Endra Yustin Ellistasari; Muhammad Eko Irawanto; Arie Kusumawardani; Nurrachmat Mulianto (International Journal Labs, 2026)
Syphilis remains a significant global health burden, particularly among high-risk populations such as men who have sex with men (MSM). A major challenge in management is the serofast state, where patients fail to achieve serological cure despite adequate treatment. The immunological mechanisms driving this, especially in the context of HIV co-infection, remain unclear. This study aims to evaluate clinical and immunological factors associated with serofast status versus serological cure. A retrospective cohort study was conducted on 40 patients diagnosed with syphilis (early latent, late latent, or secondary). Data on demographics, HIV status, CD4/CD8 counts, and pre- and post-treatment VDRL titers were analyzed. Bivariate and multivariate logistic regression analyses were performed to identify predictors of the serofast outcome. The cohort was predominantly males (90.0%) and unmarried (80.0%). HIV co-infection was identified as the sole independent predictor of the serofast state (aOR = 10.94; 95% CI: 1.72-69.65; p=0.011). While post-treatment VDRL titers significantly decreased in the total cohort, the serofast group retained significantly higher antibody levels compared to the serological cure group (p<0.001). However, no statistically significant differences were found in CD4 counts, CD8 counts, or CD4/CD8 ratios between the two groups. HIV co-infection is a strong predictor of the serofast state in syphilis patients. The lack of significant differences in quantitative cellular immune markers suggests that the persistence of antibodies may be driven by functional immune dysregulation rather than absolute T-cell depletion. These findings emphasize the need for vigilant serological monitoring in HIV-syphilis co-infected individuals.